Seasonal Variation in the consumption of biomass fuel in a rural community of Patagonia, Argentina - Morales, Daniela; Molares, Soledad; Ladio, Ana H. (Ethnobiology and Conservation, 2018)
The use of biomass as an energy resource is key to the subsistence and development of diverse rural populations throughout the world. Nevertheless, little has been considered as to how biomass consumption patterns vary throughout the year, or what strategies locals may employ. In a rural community of the Patagonian steppe, seasonal variation in domestic consumption of fuel plants was studied. Possible socioeconomic conditioning factors (i.e., size of family unit, infrastructure of dwellings, number of combustion appliances used) were analysed, and seasonal variation in the richness of plant species used was determined. Average biomass consumption was found to be 12000 kg/year/home and 1479 kg/year/per capita, with significantly higher values during winter (62.89 kg/day/home), than in summer (18.45 kg/day/home). The richness of fuel species used varied significantly during the year, and in line with biomass estimates, the highest use consensus for species was recorded during winter and autumn, with exotic species predominating. The maximum difference in species was registered in autumn, due to an increase in the stockpiling of wood bought for winter, when the preference is for high caloric value and accessible commercial price. During the year the main species used were Salix spp. and Nothofagus antarctica. The study of seasonal variation in firewood consumption contributes knowledge that can be used in detailed management of this resource, with attention being paid to differential needs as seen from a local perspective.